Canonical Foundations of Church Financing and the Plurality of Financing Systems: An Overview - Rehak, Martin (Münchener theologische Zeitschrift, 2026)
This article explores the canonical foundations for the acquisition of assets by ecclesiastical legal entities, as established in the Code of Canon Law. Through an international perspective, it surveys diverse models of church financing and proposes criteria for their evaluation. Its aim is to acquaint readers with the legal underpinnings of church financing and to offer a comprehensive overview of the varied systems employed across the globe.1 To this end, basic questions of church financing are discussed (1.), and the principles and main features of the acquisition of ecclesiastical goods are explained (2.). Subsequently, the international diversity of financing systems and criteria for their evaluation are presented (3.). A summary of the most important results concludes the article (4.).